Pengaruh Konsentrasi Gelatin Ikan Sebagai Bahan Pengikat Terhadap Kualitas dan Penerimaan Sirup - Diah Lestari Ayudiarti; Suryanti Suryanti; Tazwir Tazwir; Rosmawaty Paranginangin (Universitas Gadjah Mada, 2007)
The purpose of this research was to observe the effect of fish gelatin compared to commercial gelatin as a binder on the quality of syrup. The concentrations of gelatin added to syrup were 4, 6, 8 and 10%. The moisture content, ash content, protein content, viscosity, and microbiology test of final products were analyzed. Meanwhile, the organoleptic test was observed only for the syrup added with fish gelatin. The result showed that gelatin concentration significantly affected the viscocity of syrup. Microbiology test showed that there were no mold in this product and Escherichia coli densities were less than 3 MPN /ml while TPCs were 2,0x103 CFU/g. The syrup with 8% fish gelatine was mostly preferred by the panelists because of its color and viscosity. Moisture content, ash content, protein content, and viscosity of this syrup were 38.67%, 0,12%, 11.13%, and 122,60 cPs, respectively.